TUAN GURU HAJI MUHAMMAD NAJMUDDIN MAKMUN: KONTRIBUSI DAN PEMIKIRANNYA DALAM PENDIDIKAN DI LOMBOK TENGAH 1943-1970 M - Basarudin; Suparman Jayadi (Batuthah: Jurnal Sejarah Padaban Islam, 2024)
Just like in Java there is Kiai, in Sunda there is ajengan, in Sumatra there is buya, in Aceh there is teungku, in Madura there is bindara, and in the Nusa Tenggara region there is Tuan Guru Besar, abbreviated as TGB. He has contributions and thoughts in the educational aspect to guide the elderly and children. This article aims to find out the contributions and thoughts of TGH Muhammad Najmuddin Makmun. This research uses historical research methods which have four stages, namely, heuristics, criticism, interpretation and historiography. In this research, the results can be obtained that, TGH Muhammad Najmuddin Makmun was a scholar who was born in 1920 M and had studied in Mecca for several years with teachers there. In terms of his leadership, he is wise, charismatic, simple and does not differentiate between the social strata of society and the students he teaches, prioritizing equality. TGH Muhammad Najmuddin Makmun educational thought is to improve and increase the existence of Islamic teachings, by referring to the teachings of monotheism education so that it can be used as a process of formation or guidance based on the Islamic religion, so that students are able to carry out their humanitarian duties as well as possible and adhere firmly to strong faith and intentions. In his contribution, he put it into educating the community, both children and the elderly. Through thoriqot establishments to educate the elderly, as well as Islamic boarding schools to educate children.